2000
DOI: 10.1097/00005537-200002010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose to Otologic Structures During Head and Neck Cancer Radiation Therapy

Abstract: Background: Otologic structures are often con· tained within head and neck cancer radiation treatment ports. The dosimetry to otologic structures has not been routinely analyzed and radiation treatment planning does not currently attempt to specifically avoid the inner ear structures when dosimetry is calculated. Recent studies demonstrate that up to 30o/ o of patients experie~e sensorineural hearing loss on multimodality tlierapy with cisplatin and radiation. Methods: In the current case series, radiation dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…24) Cochlear toxicity may occur, however, during radiation therapy of head and neck cancer. 1) In the literature we found that cochlear damage increased in proportion to RT dose. Kim and Shin 25) applied a single dose of 2, 6, 10, or 15 Gy to guinea pigs, and evaluated cochleas histopathologically.…”
Section: Discussionmentioning
confidence: 93%
“…24) Cochlear toxicity may occur, however, during radiation therapy of head and neck cancer. 1) In the literature we found that cochlear damage increased in proportion to RT dose. Kim and Shin 25) applied a single dose of 2, 6, 10, or 15 Gy to guinea pigs, and evaluated cochleas histopathologically.…”
Section: Discussionmentioning
confidence: 93%
“…The cumulative risk of a significant persistent SNHL (> 15 dB) seems to stabilize within 2 years [10,21], whereas for severe SNHL (> 30 dB) the cumulative risk also continues to increase through the third and fourth year [10]. In a series with long follow-up (median of 13 years), stable rather than progressive character of SNHL was observed [18].…”
Section: Discussionmentioning
confidence: 94%
“…In any case, the cochlear dose was higher than the prescribed dose. In the series of pharyngeal and oral cavity cancer, Ondrey et al [21] observed up to 102% of prescribed dose administered to the cochlea. In the QUANTEC review, Bhandare et al [3] concluded that for conventionally fractionated radiotherapy, the mean dose to the cochlea should be limited to < 45 Gy, which was the case in all patients in our series.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal bone is at risk mainly due to its superficial location and its proximity to the aerodigestive tract. A recent study modeling radiation dosimetry to otologic structures during radiation treatment for cancers of the nasopharynx, oral cavity, oropharynx, and hypopharynx clearly demonstrated ionizing radiation delivered to the temporal bone; the eustachian tube and cochlea were sites at greatest risk, especially with radiotherapy for nasopharyngeal carcinoma (9). Osteoradionecrosis usually arises when doses greater than 60 Gy are administered and has been reported to occur anywhere from several months to 40 years after completion of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%